Combined use of pulse therapy and molecular hydrogen in rats with experimental rheumatoid arthritis: Clinical and histological evaluation of therapeutic effectiveness - Tatyana A. Berezhnova; Viktoriya V. Shishkina; Dmitry I. Esaulenko; Yelena A. Lunyova; Yelena S. Goryushkina; Angelina A. Abramyan; Kseniya S. Dyadina; Anastasia I. Chechelnitsky; Tatiana V. Samoilenko (Belgorod National Research University, 2023)
Introduction: Glucocorticosteroid therapy is the basic therapeutic option for rheumatoid arthritis; however, long-term treatment with low and medium doses is associated with the development of negative side effects. As reported, oxidative stress is crucial in the pathogenesis of rheumatoid arthritis. Therefore, pharmacotherapy that combines application of methylprednisolone pulse therapy and an aqueous molecular hydrogen solution seems to be a reasonable treatment option in these cases. Materials and Methods: The study of the effectiveness of combined pharmacotherapy for rheumatoid arthritis was carried out on mature male rats. Rheumatoid arthritis was simulated by introducing bovine type II collagen into the right knee joint. Animals of the 1st - control - group received placebo; animals of the 2nd group received molecular hydrogen-enriched water intragastrically; animals of the 3rd group received methylprednisolone solution intravenously by catheterization of the tail vein, and animals of the 4th group received water enriched with molecular hydrogenintragastrically and methylprednisolone solution intravenously. After withdrawal of animals from the experiment, microsections of their joint tissues were analysed histologically and biomarkers of the joint inflammation were detected immunohistochemically. Results and Discussion: Morphological analysis of microsections taken from animals of the 4th group evidenced effectiveness of the combined therapy based on quantitative estimation of the inflammatory biomarker expression. Dynamic polarization of M1/M2 macrophage was manifested with high quality in animals of this group. Conclusion: The search for new therapeutic options for rheumatoid arthritis is expanded due to major antioxidant substances that can reduce duration of treatment, while ensuring positive dynamics of the course of the disease.